Aedes albopictus mosquitoes host a locally structured mycobiota with evidence of reduced fungal diversity in invasive populations. (June 2019) - Luis, Patricia; Vallon, Laurent; Tran, Florence-Hélène; Hugoni, Mylène; Tran-Van, Van; Mavingui, Patrick; Minard, Guillaume; Moro, Claire Valiente
Abstract: The Asian tiger mosquito Aedes albopictus, native to Southeast Asia, has invaded a wide range of tropical and temperate areas worldwide. Recent studies pointed out that invasive populations from Europe harbored reduced bacterial microbiota compared to the native populations. Beside bacteria, mosquitoes also contain fungal communities that have so far been largely ignored. To investigate whether the mosquito invasion process displays a similar impact on fungal diversity, we compared the mycobiota structure of three autochthonous mosquito populations in Vietnam and six populations recently introduced in France and Madagascar. All mosquito populations host a locally structured fungal community and carry a "core mycobiota" dominated by yeasts. However, invasive populations from France and Madagascar harbor a lower fungal diversity compared to Vietnamese populations. These results suggest that similar factors shape the overall composition of the mosquito-associated microbiota during the invasion process as bacterial and fungal communities demonstrate a loss of diversity.